Biomass-derived carbon aerogel with skeleton genetic structure as well as preparation method and application of biomass-derived carbon aerogel
Through the preparation method of biomass-derived carbon aerogel, the problems of harsh preparation conditions and high cost in the prior art are solved, and the preparation of low-density carbon aerogels is realized, with good flexibility and electrochemical properties.
Patent Information
- Application Number
- CN202411377499.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing preparation methods of carbon aerogels have problems such as high raw material requirements, harsh experimental conditions, complex processes and high costs, making it difficult to achieve continuous production and manufacturing.
Using the preparation method of biomass-derived carbon aerogel with a skeleton genetic structure, the three steps of hydrogelization, aerogelization and carbon aerogelization include hydrothermal treatment, freeze-drying, solvent exchange and high-temperature carbonization. , low-density carbon aerogel was prepared.
A carbon aerogel with mild preparation conditions, simple process and low cost is realized, and the original excellent skeleton structure of biomass is retained, with good mechanical flexibility and electrochemical properties.
Smart Images

Figure CN119409162A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon aerogels, in particular to the technical field of biomass-derived carbon aerogels. Background Art
[0002] In recent years, with the rapid development of flexible wearable electronic devices, the research and development of flexible energy storage devices has become crucial; flexible supercapacitors have broad application prospects in the technical field of future wearable electronic devices due to their high power density, long cycle life, and low preparation and maintenance costs; electrodes, as the core components of flexible energy storage devices, affect the overall performance of flexible energy storage devices; At present, the research focus in the industry is how to develop low-cost and high-energy-density flexible electrode materials without sacrificing overall electrochemical performance.
[0003] Among the many electrode materials, carbon materials are widely used in the preparation of electrodes for flexible supercapacitors due to their wide sources, low cost, excellent conductivity and high chemical stability; however, due to the limitations of the precursor structure and preparation process, the mechanical flexibility of carbon materials is not ideal (for this reason, it is urgent to explore the preparation process of highly flexible carbon material electrodes).
[0004] Carbon aerogels have attracted extensive attention due to their light weight, low density and high porosity structural characteristics (these unique structural characteristics make carbon aerogel materials have good mechanical flexibility); in addition, carbon aerogels usually have a three-dimensional mesh porous structure, which is conducive to accelerating the transmission of ions / electrons; however, the existing carbon aerogel preparation methods not only require the use of ultra-low temperature freeze-drying technology, but also require the use of relatively expensive organic precursors or biomacromolecules and graphene and carbon nanotubes and other materials for cross-linking and compounding, such as the preparation and application of graphene oxide carbon aerogel with announcement number CN112687476B, a full carbon graphene aerogel and its preparation method with announcement number CN110562964B, and a carbon nanotube aerogel and its preparation and application with announcement number CN108178144B, which have the disadvantages of high raw material requirements, harsh experimental conditions, complex processes and high costs (i.e., it is difficult to achieve continuous production and manufacturing); that is, it is of great significance to explore a carbon aerogel preparation method with a wide source of raw materials, a mild preparation environment and a simple process.
[0005] Among the numerous carbon materials, biomass-derived carbon materials are widely available, low in cost and have excellent electrochemical energy storage properties; porous biomass such as straw cores, grapefruit peels, watermelon peels and durian shells are potential carbon aerogel precursor materials; however, there is currently very little research on the preparation process for converting such biomass materials into carbon aerogels; how to use an economical and efficient preparation process to convert these structurally advantageous, cheap porous biomass materials into carbon aerogel materials with good mechanical flexibility and electrochemical advantages is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the prior art and to propose a biomass-derived carbon aerogel with a skeleton genetic structure and a preparation method and application thereof. The prepared carbon aerogel can not only retain the original excellent skeleton structure of the biomass, but also has mild preparation conditions, simple preparation process and low preparation cost.
[0007] To achieve the above object, the present invention is implemented through the following technical solutions: The method for preparing biomass-derived carbon aerogel having a skeleton genetic structure comprises the following steps: a) Hydrogelation: hydrothermally treating porous biomass to obtain biomass hydrogel; b) Aerogelization: After freezing the biomass hydrogel to obtain biomass cryogel, the biomass cryogel is subjected to solvent exchange treatment and drying treatment in sequence to obtain biomass aerogel; c) Carbon aerogelization: The biomass aerogel is carbonized to obtain biomass carbon aerogel.
[0008] Preferably, in step a), the water absorption structure of the porous biomass is a sponge-like structure or a cotton-like structure; such biomass materials usually have excellent pore structures or tubular channels, and substances in the pores or tubular channels can be removed by processes such as freeze-drying, thereby retaining the biomass skeleton (i.e., being able to form an excellent carbon aerogel structure); the porous biomass can also be pre-cleaned before the hydrothermal treatment.
[0009] Furthermore, the porous biomass is one or a combination of passion fruit shell, broad bean peel, wax apple, cantaloupe peel, banana peel, grapefruit peel, watermelon peel, straw core and durian shell.
[0010] Preferably, in step a), the hydrothermal treatment is to hydrothermally react the porous biomass in deionized water at a temperature of 100 to 200° C. for 8 to 12 hours; during the hydrothermal process, water molecules can be fully filled in the skeleton structure of the biomass solid; after the hydrothermal treatment, the biomass hydrogel can be cooled to room temperature by naturally standing or circulating cold water, and then the surface of the biomass hydrogel can be repeatedly washed to remove impurities after filtering out the biomass hydrogel.
[0011] Preferably, in step b), the freezing treatment is to freeze the biomass hydrogel at a temperature of -10 to -30°C for at least 12 hours.
[0012] Preferably, in step b), the solvent exchange treatment is to thaw the biomass cryogel in a solvent having a capillary force smaller than that of water molecules for at least three times and each time for no less than 20 minutes, so that the water molecules are fully exchanged; wherein, replacing water molecules with a solvent having a smaller capillary force can effectively reduce the problem of structural shrinkage caused by hydrogen bonds and capillary forces in the drying process of the biomass, thereby better maintaining the genetic skeleton structure of the biomass; during the solvent exchange treatment, ultrasonic oscillation can also be used to accelerate the solvent exchange.
[0013] Furthermore, the solvent having a capillary force smaller than that of water molecules is one or a combination of ethanol, methanol, propanol, isopropanol and octane.
[0014] Preferably, in step b), the drying treatment is to dry the biomass cryogel after the solvent exchange at a temperature of 25 to 50° C. for 5 to 12 hours in a normal pressure environment; such a relatively low temperature environment drying treatment can slowly evaporate the solvent molecules, thereby reducing the structural collapse during the formation of the biomass aerogel, which is beneficial to maintaining the original skeleton structure of the biomass.
[0015] Preferably, in step c), the carbonization treatment is to first heat the biomass aerogel to 600-800° C. at a rate of 5-10° C. / min and then keep the temperature for 20-40 min.
[0016] Furthermore, in step c), the carbonization treatment is carried out in a CO2 atmosphere; wherein the CO2 active atmosphere is beneficial to increasing the surface porosity of the carbon aerogel, thereby forming an excellent porous structure.
[0017] Biomass-derived carbon aerogel with a skeleton genetic structure, prepared by the above preparation method, with a bulk density of less than 0.1 g / cm 3 It also has the morphological characteristics of a hierarchical porous structure and a carbon nanosphere network encapsulating the original biomass genetic skeleton structure.
[0018] Biomass-derived carbon aerogels with backbone genetic architecture for applications in flexible electrodes.
[0019] Beneficial effects of the present invention: 1) In view of the problems of high precursor cost, complex preparation process and harsh preparation conditions of existing carbon aerogels, the present invention uses biomass with high water content and / or water-absorbing tissue (such as sponge or cotton-like) as the carbon source, and adopts conventional gel freezing, solvent exchange, environmental drying and high-temperature carbonization process to prepare low-density carbon aerogel, which can not only retain the original excellent skeleton structure of biomass, but also has mild preparation conditions, simple preparation process and low preparation cost (on the one hand, no expensive instruments and consumables are required, and on the other hand, cheap biomass materials with unique structure are used as carbon aerogel precursors, thereby greatly reducing the preparation cost of carbon aerogel); 2) The biomass-derived carbon aerogel electrode prepared by the present invention has good mechanical flexibility, and the electrochemical performance of the flexible supercapacitor is almost unaffected at different bending angles. The biomass-derived carbon aerogel material with a genetic skeleton structure has excellent specific capacitance and rate performance when used as a flexible symmetric supercapacitor electrode material, which provides a new idea for the synthesis of converting cheap porous biomass materials into advanced energy storage flexible electrode materials; 3) The present invention can greatly reduce the occurrence of collapse by using a solvent with a capillary force smaller than that of water molecules to perform solvent exchange, low-temperature drying, and carbonization treatment under a CO2 active atmosphere on the biomass hydrogel, thereby ensuring that the carbon aerogel has a rich pore structure.
[0020] The features and advantages of the present invention will be described in detail through embodiments in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a process flow chart of a method for preparing a biomass-derived carbon aerogel having a skeleton genetic structure; Figure 2 It is a physical picture of the passion fruit shell hydrogel, passion fruit shell aerogel and passion fruit shell carbon aerogel of Example 1; Figure 3 is a SEM image of the passion fruit shell of Example 1; Figure 4 1 is a SEM image of the PFSCA of Example 1 and the PFSC of Comparative Example 3; Figure 5 is a N2 adsorption-desorption curve diagram of the PFSCA of Example 1; Figure 6 are the XRD and Raman spectra of the PFSCA of Example 1 and the PFSC of Comparative Example 3; Figure 71 is the XPS spectrum of the PFSCA of Example 1 and the PFSC of Comparative Example 3; Figure 8 1 is a comparison diagram of the electrochemical performance of the PFSCA of Example 1 and the PFSC of Comparative Example 3; Fig. 9 is an electrochemical performance curve diagram of the PFSCA of Example 1 at different bending angles; Fig.10 This is a graph showing the electrochemical performance of the symmetrical flexible supercapacitor assembled with the PFSCA of Example 1. DETAILED DESCRIPTION
[0022] Embodiment 1: See also Figure 1 , using biomass-derived carbon aerogels with skeleton genetic structures to prepare electrodes for flexible supercapacitors and conduct performance tests, the specific steps are as follows: Step 1: First, rinse the passion fruit shell with deionized water to remove surface impurities, and then cut it into 2x2cm block samples; then, place the block sample in a stainless steel reactor with a polytetrafluoroethylene liner and hydrothermally react at 180°C for 10 hours; after the hydrothermal reaction, repeatedly rinse with a large amount of deionized water to remove surface impurities of the sample, and obtain passion fruit shell hydrogel (actual picture as shown in the figure) Figure 2 as shown in part (a) of the figure); Step 2: Place the passion fruit shell hydrogel in a refrigerator and freeze it at -25°C for 12 hours to form passion fruit shell cryogel; first immerse the passion fruit shell cryogel in ethanol to thaw and use ethanol as a solvent for ultrasonic replacement three times, each time for 30 minutes, and then place the passion fruit shell cryogel after the solvent exchange in an oven and dry it at 30°C for 10 hours to obtain passion fruit shell aerogel (denoted as PFSA, the actual picture is as shown in the figure) Figure 2 as shown in part (b) of the figure); Step 3: Place PFSA in a tube furnace and heat it to 700°C at a rate of 10°C / min in a CO2 atmosphere and keep it warm for 30 min; then, wash and dry it with 1 M hydrochloric acid, anhydrous ethanol and deionized water in sequence to obtain passion fruit shell carbon aerogel (denoted as PFSCA, as shown in the figure) Figure 2 as shown in part (c) of the figure); Step 4: PFSCA, acetylene black and polytetrafluoroethylene were mixed in a mass ratio of 7:2:1 and ground into an electrode film with the aid of isopropanol; then, the electrode film was cut into 1 cm × 1 cm electrode sheets and placed in a drying oven together with 1 cm × 2 cm nickel foam, and then dried at 105 ° C for 8 h; then, the electrode sheet was pressed on one end of the nickel foam (pressure of 6 MPa, maintained for 30 s) to obtain a passion fruit shell carbon aerogel electrode (referred to as PFSCA electrode); Step 5: The passion fruit shell carbon aerogel electrode, platinum electrode and saturated calomel electrode were used as working electrode, counter electrode and reference electrode respectively, and the electrochemical test was carried out using 6 M / L KOH solution as electrolyte. The specific capacitance of the passion fruit shell carbon aerogel electrode was measured to be 167 F / g (current density = 1 A / g), the charge transfer internal resistance was 1.3 Ω and the working voltage window was 1.05 V on the electrochemical workstation; Step 6: The passion fruit shell carbon aerogel electrode was symmetrically immersed in the PVA-KOH gel electrolyte (the active material parts were placed opposite to each other) and dried at room temperature overnight to obtain a passion fruit shell derived supercapacitor (denoted as FASSC); wherein the PVA-KOH gel electrolyte was prepared by first adding 3g of PVA (polyvinyl alcohol) to 30ml of deionized water and stirring in a water bath at 90°C until the solution was clear, and then slowly dripping 10ml of 6 M / L KOH into the stirring PVA aqueous solution and continuing to stir for 30min; Step 7: Under the two-electrode system, the voltage window of the passion fruit shell-derived supercapacitor was measured to be 2 V, and the specific energy density was 30.6 Wh / kg at a high power density of 2000 W / kg.
[0023] Figure 3 is the SEM image of passion fruit shell without any treatment. Figure 4 The second row of images are SEM images of biomass-derived carbon aerogels (i.e., PFSCA) with skeleton genetic structure made from passion fruit shells, and show the skeleton structure and surface morphology before and after treatment respectively; Figure 4 It can be seen that PFSCA has an excellent hierarchical porous structure, retaining the spiral hollow tubular structure of the original biomass, and the morphological characteristics of the tubular channel surface formed by the carbon nanosphere network coating; the bulk density of PFSCA is less than 0.056g / cm 3 , and contains rich heteroatoms (N: 1 at%; O: 6.2 at%).
[0024] In addition, the N2 adsorption and desorption curves of PFSCA and the electrochemical performance curves at different bending angles are shown in Figure 2. Figure 5 and Fig. 9 As shown (in Fig. 9 In the figure, part (a) shows the GCD curve of PFSCA at different bending angles, and part (b) shows the CV curve of the GCD curve of PFSCA at different bending angles); the electrochemical performance curve of the symmetrical flexible supercapacitor assembled by PFSCA is shown in the figure Fig.10 As shown (in Fig.10In the figure, part (a) shows the CV curves at different scan rates, part (b) shows the GCD curves at different current densities, part (c) shows the cycling ability, and part (d) shows the specific power density and specific energy density curves).
[0025] The lower density makes the PFSCA electrode have excellent mechanical flexibility; the hollow tubular skeleton structure inherited from biomass and the surface carbon nanosphere complex structure shorten the transmission distance of ions / electrons in the electrolyte, which is beneficial to reduce the internal resistance of the flexible electrode; the self-doping of N, O atoms can effectively enhance the pseudocapacitive effect of the material, which is beneficial to improve the electrochemical energy storage effect of the flexible electrode; therefore, this electrode material has a high voltage window of 1.05V and a very small charge transfer resistance (1.3Ω) in aqueous electrolyte, and the specific capacitance can reach 167 F / g at 1 A / g in the three-electrode system (it still has a specific capacity of more than 100F / g at a high current density of 10 A / g); the flexible symmetric supercapacitor assembled using the above-mentioned flexible electrodes has a high voltage window of 2V and can withstand 2000 W kg -1 The specific energy density can still reach 30.6 Wh kg at high power density. -1 .
[0026] Embodiment 2: In this embodiment, in step 1, the block sample is placed in a stainless steel reactor with a polytetrafluoroethylene liner and subjected to a hydrothermal reaction at a temperature of 150° C. for 10 hours; the rest is the same as in embodiment 1.
[0027] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 160 F / g (current density = 1 A / g), a charge transfer internal resistance of 1.5 Ω and a working voltage window of 1.05 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 2 V and a specific energy density of 27.7 Wh / kg at a high power density of 1994.4 W / kg.
[0028] This embodiment shows that lowering the hydrothermal reaction temperature leads to a decrease in the specific capacitance of the carbon aerogel electrode and an increase in the charge transfer resistance, while the specific power density and energy density of the composed symmetric flexible supercapacitor decrease slightly.
[0029] Embodiment three: In this embodiment, in step 2, the passion fruit shell cryogel is immersed in isopropanol to thaw and is ultrasonically replaced three times with isopropanol as a solvent for 30 minutes each time; the rest is the same as in embodiment 1.
[0030] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 172 F / g (current density = 1 A / g), a charge transfer internal resistance of 1.7 Ω and a working voltage window of 1 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 2 V and a specific energy density of 31.7 Wh / kg at a high power density of 2002.1 W / kg.
[0031] This example shows that replacing the exchange solvent with isopropanol will lead to an increase in the specific capacitance of the carbon aerogel electrode, a decrease in the voltage window, and an increase in the charge transfer resistance, while the specific power density and energy density of the composed symmetric flexible supercapacitor will be slightly increased.
[0032] Embodiment 4: In this embodiment, in step 2, the passion fruit shell hydrogel is placed in a refrigerator and frozen at -20°C for 12 hours to form passion fruit shell cryogel; the rest is the same as in embodiment 1.
[0033] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 157 F / g (current density = 1 A / g), a charge transfer internal resistance of 1.4 Ω and a working voltage window of 1.05 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 2 V and a specific energy density of 26.7 Wh / kg at a high power density of 2002.5 W / kg.
[0034] This embodiment shows that increasing the freezing temperature to -20°C will cause the specific capacitance of the carbon aerogel electrode to decrease and the charge transfer resistance to increase, while the specific power density of the composed symmetric flexible supercapacitor will increase slightly, but the specific energy density will decrease.
[0035] Embodiment five: In this embodiment, in step 2, the passion fruit shell cryogel is immersed in ethanol to thaw and ultrasonically replaced five times with ethanol as a solvent for 30 minutes each time; the rest is the same as in embodiment 1.
[0036] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 180 F / g (current density = 1 A / g), a charge transfer internal resistance of 0.9 Ω and a working voltage window of 1.05 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 2.1 V and a specific energy density of 36.8 Wh / kg at a high power density of 2208 W / kg.
[0037] This example shows that increasing the number of solvent exchanges to 5 times results in a carbon aerogel electrode having a higher specific capacitance and a lower charge transfer resistance, and the composed symmetric flexible supercapacitor has a higher specific power density and specific energy density.
[0038] Embodiment six: In this embodiment, in step 2, the passion fruit shell cryogel after the solvent exchange is placed in an oven to be dried at 50° C. for 10 hours; the rest is the same as in embodiment 1.
[0039] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 150 F / g (current density = 1 A / g), a charge transfer internal resistance of 1.2 Ω and a working voltage window of 1 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 1.8 V and a specific energy density of 20.3Wh / kg at a high power density of 1827 W / kg.
[0040] This embodiment shows that when the ambient drying temperature is increased to 50°C, the carbon aerogel electrode has a lower specific capacitance, voltage window and charge transfer resistance, and the specific power density and specific energy density of the composed symmetric flexible supercapacitor decrease significantly.
[0041] Embodiment seven: In this embodiment, in step 3, the PFSA is placed in a tube furnace and heated to 750° C. at a rate of 10° C. / min in a CO 2 atmosphere and then kept at this temperature for 30 minutes; the rest is the same as in embodiment 1.
[0042] In addition, the passion fruit shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 165 F / g (current density = 1 A / g), a charge transfer internal resistance of 1.1 Ω and a working voltage window of 1.05 V measured in an electrochemical workstation; the passion fruit shell-derived supercapacitor obtained in this embodiment has a voltage window of 2 V and a specific energy density of 32.2 Wh / kg at a high power density of 1998.6 W / kg.
[0043] This embodiment shows that when the carbonization temperature is increased to 750°C, the specific capacitance of the carbon aerogel electrode does not change significantly, the charge transfer resistance decreases slightly, and the specific power density and specific energy density of the composed symmetric flexible supercapacitor increase.
[0044] Embodiment eight: In this embodiment, in step 1, the broad bean husks are first rinsed with deionized water to remove surface impurities; the rest is the same as in embodiment 1.
[0045] In addition, the broad bean horn shell carbon aerogel electrode obtained in this embodiment has a specific capacitance of 143 F / g (current density = 1 A / g), a charge transfer internal resistance of 2.8 Ω and a working voltage window of 1 V measured in an electrochemical workstation; the broad bean horn shell derived supercapacitor obtained in this embodiment has a voltage window of 2 V, and has a specific energy density of 23.3Wh / kg at a high power density of 1997.1 W / kg.
[0046] This embodiment shows that when the biomass is replaced with broad bean horn shell, the carbon aerogel electrode has a lower specific capacitance and voltage window and a higher charge transfer resistance, and the specific power density and specific energy density of the composed symmetric flexible supercapacitor decrease.
[0047] Comparative Example 1: The operation is basically the same as that of Example 1, except that the comparative example does not undergo solvent exchange treatment, but directly subjecting the hydrogel to ambient drying.
[0048] The result shows that the structure of the biomass aerogel sample obtained in this comparative example is severely collapsed.
[0049] Comparative Example 2: The operation is basically the same as that of Example 1, except that the ambient drying temperature of this comparative example is 80°C.
[0050] The result shows that the structure of the biomass aerogel sample obtained in this comparative example is severely collapsed.
[0051] Comparative Example 3: This comparative example adopts direct pyrolysis method to prepare biomass-derived carbon material, and the specific steps are as follows: Step 1: drying the washed passion fruit shell at 100° C., and then crushing the passion fruit shell to obtain a powdered solid; Step 2: Screening out a portion with a particle size of < 0.25 mm from the passion fruit shell powder solid and placing it in a tube furnace for pyrolysis, and the pyrolysis and washing conditions are the same as those in Example 1 to obtain a passion fruit shell derived carbon material (denoted as PFSC); Step 3: The preparation process of the electrode is the same as that of Example 1 to obtain a PFSC electrode; Step 4: The test device is the same as in Example 1. The specific capacitance of the PFSC electrode is measured on an electrochemical workstation to be 170 F / g (current density = 1 A / g), the charge transfer internal resistance is 12 Ω, and the operating voltage window is 1.05 V; Step 5: The preparation process of the supercapacitor is the same as that of Example 1, to obtain a PFSC supercapacitor; Step 6: The test method is the same as that in Example 1. The voltage window of the PFSC supercapacitor is measured to be 2 V, and the specific energy density is 31.1 Wh / kg at a high power density of 1999.2 W / kg.
[0052] Figure 4 The first row of images are SEM images of PFSC, and they show the skeleton structure and surface morphology before and after treatment respectively; in addition, Figure 6 , Figure 7 and Figure 8 The XRD and Raman spectra, XPS spectra and electrochemical performance curves of the PFSCA of Example 1 and the PFSC of Comparative Example 3 are shown respectively (in Figure 8 In the figure, part (a) is the CV curve of PFSCA of Example 1 and PFSC of Comparative Example 3 at 5 mV / s; part (b) is the CV curve of PFSCA electrode of Example 1 at different scan rates; part (c) is the GCD curve of PFSCA of Example 1 and PFSC of Comparative Example 3 at 1 A / g; part (d) is the GCD curve of PFSCA electrode of Example 1 at different current densities; part (e) is the rate performance of PFSCA of Example 1 and PFSC of Comparative Example 3; part (f) is the electrochemical impedance curve of PFSCA of Example 1 and PFSC of Comparative Example 3).
[0053] The above electrochemical test curve analysis shows that the CV curves of PFSC and PFSCA are both relatively regular rectangles, which indicates that the samples show good double-layer capacitance characteristics in 6 M KOH electrolyte; when the scan rate increases, the CV curve of PFSC gradually deviates from the rectangle, while the CV curve of PFSCA can still maintain its original shape, which indicates that PFSCA has better redox reversibility; PFSC and PFSCA have good redox reversibility at 1A g -1 The GCD curves at current densities of 1A g are basically symmetrical triangles with no obvious voltage drop, indicating that both samples have excellent Coulomb efficiency and small internal resistance. -1 At a current density of 1.34 W, the discharge specific capacitance of PFSC and PFSCA is 170 F g -1 and 167 F g -1 , which shows that the capacitance performance of the two is very similar, but PFSCA has a better rate performance; PFSCA can still retain 70% of its specific capacity after increasing its current density tenfold, while PFSC only retains 56%; in addition, PFSCA (R ct : 1.3Ω) is much smaller than PFSC (R ct : 12Ω), which indicates that PFSCA has better conductivity.
[0054] The above embodiments are intended to illustrate the present invention, not to limit the present invention. Any solution that is a simple transformation of the present invention belongs to the protection scope of the present invention.
Claims
1. A method for preparing a biomass-derived carbon aerogel having a skeleton genetic structure, characterized in that: The steps include: a) Hydrogelation: hydrothermally treating porous biomass to obtain biomass hydrogel; b) Aerogelization: After freezing the biomass hydrogel to obtain biomass cryogel, the biomass cryogel is subjected to solvent exchange treatment and drying treatment in sequence to obtain biomass aerogel; c) Carbon aerogelization: The biomass aerogel is carbonized to obtain biomass carbon aerogel.
2. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step a), the water absorption structure of the porous biomass is a sponge-like structure or a cotton-like structure.
3. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step a), the hydrothermal treatment is to hydrothermally react the porous biomass in deionized water at a temperature of 100 to 200° C. for 8 to 12 hours.
4. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step b), the freezing treatment is to freeze the biomass hydrogel at a temperature of -10 to -30°C for more than 12 hours.
5. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step b), the solvent exchange treatment is to thaw the biomass cryogel by immersing it in a solvent with a capillary force smaller than that of water molecules for at least three times and each time for no less than 20 minutes.
6. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step b), the drying treatment is to dry the biomass cryogel after the solvent exchange at a temperature of 25 to 50° C. for 5 to 12 hours in a normal pressure environment.
7. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 1, characterized in that: In step c), the carbonization treatment is to first heat the biomass aerogel to 600-800° C. at a rate of 5-10° C. / min and then keep the temperature for 20-40 minutes.
8. The method for preparing the biomass-derived carbon aerogel having a skeleton genetic structure according to claim 7, characterized in that: In step c), the carbonization treatment is carried out in a CO2 atmosphere.
9. A biomass-derived carbon aerogel having a skeleton genetic structure, prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Bulk density less than 0.1 g / cm 3 It also has the morphological characteristics of a hierarchical porous structure and a carbon nanosphere network encapsulating the original biomass genetic skeleton structure.
10. Use of the biomass-derived carbon aerogel with a skeleton genetic structure as claimed in claim 9 in a flexible electrode.
Citation Information
Patent Citations
A carbon nanotube aerogel, its preparation and application
CN108178144B
A full-carbon graphene aerogel and its preparation method
CN110562964B
Preparation and application of graphene oxide carbon aerogel
CN112687476B